Study of Early Onset Schizophrenia: Associations of GRIN2A and GRIN2B Polymorphisms - Evgeniya G. Poltavskaya; Olga Yu. Fedorenko; Elena G. Kornetova; Anton J. M. Loonen; Alexander N. Kornetov; Nikolay A. Bokhan; Svetlana A. Ivanova (Life, 2021)
Background: Schizophrenia is a complex mental disorder with a high heritability. Dysfunction of the N-methyl-D-aspartate (NMDA)-type glutamate receptors may be involved in the pathogenesis of schizophrenia. In this study, we examined the contribution of GRIN2A and GRIN2B (Glutamate Ionotropic Receptor NMDA Type Subunit 2A/2B) polymorphisms to the clinical features of schizophrenia, such as the leading symptoms, the type of course, and the age of onset. Methods: A population of 402 Russian patients with schizophrenia from the Siberian region was investigated. Genotyping of seventeen single-nucleotide polymorphisms (SNPs) in GRIN2A and GRIN2B was performed using QuantStudio™ 3D Digital PCR System Life Technologies amplifier using TaqMan Validated SNP Genotyping Assay kits (Applied Biosystems). The results were analyzed using Chi-square and the Fisher’s exact tests. Results: We found an association of GRIN2A rs7206256 and rs11644461 and GRIN2B rs7313149 with the early onset (before the age of 18 years old) schizophrenia. We did not reveal any associations of GRIN2A and GRIN2B polymorphisms with leading (positive vs. negative) symptoms or type of course (continuous vs. episodic) of schizophrenia. Conclusions: In the study, we confirmed the involvement of the GRIN2A and GRIN2B genes in the early onset of schizophrenia in a Russian population of the Siberian region.